1978
DOI: 10.1073/pnas.75.4.1801
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characteristics and organization of chlorophyll in marine dinoflagellates

Abstract: The photosystem I reaction center complex, the P -700-chlorophyll a -protein, has been isolated from the photosynthetic membranes of two marine dinoflagellates, Gonyaulax polyedra and Glenodinium sp., by detergent solubilization with Triton X-100. The complexes isolated from the two species were indistinguishable, exhibiting identical absorption properties (400-700 nm) at both room (300 K) and low (77 K) temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Previous studies from our laboratory (19,21) and that of Grumbach et al (9) (4), however, it has been suggested that chang,es in the characteristics of PSU are associated with changes in piiotosynthetic response (3,5,11,20).…”
mentioning
confidence: 71%
“…Previous studies from our laboratory (19,21) and that of Grumbach et al (9) (4), however, it has been suggested that chang,es in the characteristics of PSU are associated with changes in piiotosynthetic response (3,5,11,20).…”
mentioning
confidence: 71%
“…Dinoflagellates contain a single type of chl c which serves as the accessory pigment to the chl a-protein complex, common in dinoflagellates as the peridinin (Boczar & Prézelin, 1987) but has not yet been investigated in Pyrodinium. In Gonyaulax and Glenodinium, chls a and c occur in a molar ratio of 4 : 1 (Prézelin & Alberte, 1978) while in Pyrodinium, it occurs in a ratio of~5 : 1 (ng cell −1 ) for both vegetative cells grown in f/2 medium and low total nutrient. The absence of chl b in either stage of the dinoflagellate corroborates the findings of Strain et al (1943) who claimed that it was not observed in majority of marine plants with chl c.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence presented PSU characteristics have been determined. Prezelin & here indicates that the 3 species of Symbiodinium ana- Alberte (1978) reported chl a-based PSU-P,,, sizes of lyzed effectively modify their photosynthetic machin-600 for the free-living dinoflagellates Glenodinium sp. ery in response to changes in photon flux density.…”
Section: Consistent With Previous Observationsmentioning
confidence: 99%